Advanced Electrochemical Performance of NiWO4/Graphene Oxide as Cathode Material for Zinc Ion Battery - Likai Deng; Shifa Wang (Energies)
The NiWO4 powder was prepared by combining the hydrothermal method with calcination. Several studies have demonstrated that the NiWO4/graphene oxide composite can enhance the electrochemical performance of the NiWO4 material. However, no studies have investigated the use of NiWO4/graphene oxide composite material as the cathode material in zinc-ion batteries. The successful preparation of the NiWO4/graphene oxide composite material is verified by various characterization techniques. The NiWO4/graphene oxide composite, which is meant to be a cathode material, is fabricated into electrode sheets and incorporated into CR2025 coin cells for electrochemical assessment. The experimental results indicate that the material exhibits a high charge–discharge specific capacity with high rates. At a current density of 0.1 A g−1, it has a specific capacity of 490.2 mA h g−1. Even after 2000 charge–discharge cycles at a current density of 1 A g−1, the capacity remains constant at 75.2%. Through calculations, it is found that the charge storage is mainly contributed to by pseudocapacitance.